Rapid removal of anionic organic dye from contaminated water using a poly(3-aminobenzoic acid/graphene oxide/cobalt ferrite) nanocomposite low-cost adsorbent via adsorption techniques - Bashdar A. M. Babakir; Layth I. Abd Ali; Hani K. Ismail (Arabian Journal of Chemistry, 2022)
This research study aims to remove hazardous anionic azo dyes (Congo red (CR)) from aqueous solutions via a simple adsorption method using a poly(3-aminobenzoic acid/graphene oxide/cobalt ferrite) nanocomposite (P3ABA/GO/CoFe2O4) as a novel and low-cost nanoadsorbent, as synthesized by a simple and straightforward polymerization method. Typically, 3-aminobenzoic acid (3ABA), as monomer, was chemically polymerized with graphene oxide (GO) and cobalt ferrite (CoFe2O4) in an aqueous acidic medium containing an ammonium persulfate initiator. The adsorbent P3ABA/GO/CoFe2O4 nanocomposite was characterized using various techniques such as Fourier transform infrared spectroscopy, X-ray diffraction, thermogravimetric analysis, transmission electron microscopy, scanning electron microscopy, energy-dispersive analysis by X-ray and Brunauer–Emmett–Teller, vibrating sample magnetometer, and zeta potential techniques. These techniques confirmed the interaction between the poly(3-aminobenzoic acid) with GO and CoFe2O4 due to the presence of π-π interactions, hydrogen bonding, and electrostatic forces. Herein, the removal efficiency of dye from aqueous solution by the adsorbent was studied according to several parameters such as the pH of the solution, dye concentration, dosage of adsorbent, contact time, and temperature. The adsorption of the dye was fitted using a Langmuir model (R2 between 0.9980 and 0.9995) at different temperatures, and a kinetic model that was pseudo-second order (R2 = between 0.9993 and 0.9929) at various initial concentrations of CR dye. In addition, the data revealed that the P3ABA/GO/CoFe2O4 nanocomposite exhibited a high adsorption capacity (153.92 mg/g) and removal for CR dye (98 %) at pH 5. Thermodynamic results showed the adsorption process was an endothermic and spontaneous reaction. It was found that, in terms of reusability, the P3ABA/GO/CoFe2O4 adsorbent can be used for up to six cycles. In this study, P3ABA/GO/CoFe2O4 nanocomposites were found to be low cost, and have an excellent removal capability and fast adsorption rate for CR from wastewater via a simple adsorption method. Moreover, this adsorbent nanocomposite could be simply separated from the resultant solution and recycled.